2021
DOI: 10.1097/aog.0000000000004352
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Outcomes of Sentinel Lymph Node Mapping in Women With Atypical Endometrial Hyperplasia

Abstract: OBJECTIVE: To examine the utilization, morbidity, and cost of sentinel lymph node mapping in women undergoing hysterectomy for complex atypical endometrial hyperplasia. METHODS: Women with complex atypical endometrial hyperplasia who underwent hysterectomy from 2012 to 2018 in the Perspective database were examined. Perioperative morbidity, mortality, and cost were examined based on performance of sentinel lymph node mapping, lymph node dissection or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…13 Using a previously defined methodology, perioperative complications were classified as intraoperative (ureteral, bladder, intestinal, vascular or other injuries), surgical site (abscess, gastrointestinal complications, haemorrhage or other wound complications) and medical (urinary complications, deep vein thrombosis, pulmonary embolism, pulmonary complications, cardiovascular complications, neurological complications, shock and infection). 13,15 A merged measure of any complication (intraoperative, surgical site or medical complication) was also analysed. Blood transfusions were defined as the receipt of red blood cells during the index hospitalisation.…”
Section: Outcomes and Covariatesmentioning
confidence: 99%
“…13 Using a previously defined methodology, perioperative complications were classified as intraoperative (ureteral, bladder, intestinal, vascular or other injuries), surgical site (abscess, gastrointestinal complications, haemorrhage or other wound complications) and medical (urinary complications, deep vein thrombosis, pulmonary embolism, pulmonary complications, cardiovascular complications, neurological complications, shock and infection). 13,15 A merged measure of any complication (intraoperative, surgical site or medical complication) was also analysed. Blood transfusions were defined as the receipt of red blood cells during the index hospitalisation.…”
Section: Outcomes and Covariatesmentioning
confidence: 99%
“…A 2021 retrospective study found that performance of lymph node evaluation in patients who underwent hysterectomy for complex endometrial hyperplasia with atypia increased from 0.8% to 14.0% between 2012 and 2018 in the United States (a 17.5-fold increase). 2 The objective of the study was to examine the national-level trends and characteristics of surgical nodal evaluation at hysterectomy for endometrial hyperplasia with or without atypia.…”
Section: Introductionmentioning
confidence: 99%
“…For some preinvasive gynecological conditions, such as atypical endometrial hyperplasia, there has been a trend towards increasing utilization of surgical nodal evaluation with sentinel lymph node biopsy at the time of hysterectomy. 24 Collectively, these recent trends are likely driven by the increased availability of sentinel lymph node mapping which decreases the morbidity of nodal evaluation.…”
Section: Resultsmentioning
confidence: 99%